ANALISIS PENANAMAN KARAKTER PEDULI SOSIAL MELALUI PROGRAM BAKTI SOSIAL DI SEKOLAH DASAR - Ahmad Fitroni; Badruli Martati; Kunti Dian Ayu Afiani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the cultivation of social care character through a social service program at SD Negeri Bulak Rukem 1 Surabaya. The research method used is qualitative with data collection techniques in the form of observation, interviews, and documentation. The data analysis process in this qualitative research includes data collection, reduction, data presentation, and conclusion drawn. The results of the study show that indicators of social care character, such as empathy, cooperation, manners, tolerance, and social action have been well implemented by the majority of students. The donation program at social services, the infaq box on Friday Blessings, is an effective means of instilling the value of social care. These findings show that the formation of social care character plays an important role in creating a generation that is more caring and responsible for the surrounding community.